Respostas

2014-04-05T23:11:53-03:00
B/4=c/2                                                               b+c=90
                                                                           b=90-c

substituindo o valor de "b"                    substituindo o valor de c na equação b=90-c
90-c/4=c/2                                                b=90-c
4c=2.(90-c)                                               b=90-30
4c+2c=180                                                b=60
6c=180
c=180/6
c=30

2014-04-05T23:17:23-03:00
Se b/4 = c/2 => b = 4c/2 => b = 2c, substituindo em: 

b+c = 90 => 2c + c = 90 => 3c = 90 => c = 90/3 => c = 30.

Se c = 30, logo b = 2c => b = 2.30 => b = 60